2008
DOI: 10.1021/bm701430y
|View full text |Cite
|
Sign up to set email alerts
|

Substrata Mechanical Stiffness Can Regulate Adhesion of Viable Bacteria

Abstract: The competing mechanisms that regulate adhesion of bacteria to surfaces and subsequent biofilm formation remain unclear, though nearly all studies have focused on the role of physical and chemical properties of the material surface. Given the large monetary and health costs of medical-device colonization and hospital-acquired infections due to bacteria, there is considerable interest in better understanding of material properties that can limit bacterial adhesion and viability. Here we employ weak polyelectrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
187
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(210 citation statements)
references
References 64 publications
9
187
4
Order By: Relevance
“…The plasma treatment has altered the mechanical properties of the top-most surface of the PDMS (Table 2). A positive correlation between substrate stiffness and the initial attachment of the bacteria Staphylococcus epidermis has been reported [46]. However this correlation does not apply in the case of the present study as lower bacteria attachment was observed for the plasma treated (harder) surface.…”
Section: Marine Bacteria: Attachment and Adhesion Strengthcontrasting
confidence: 58%
See 1 more Smart Citation
“…The plasma treatment has altered the mechanical properties of the top-most surface of the PDMS (Table 2). A positive correlation between substrate stiffness and the initial attachment of the bacteria Staphylococcus epidermis has been reported [46]. However this correlation does not apply in the case of the present study as lower bacteria attachment was observed for the plasma treated (harder) surface.…”
Section: Marine Bacteria: Attachment and Adhesion Strengthcontrasting
confidence: 58%
“…cally reduced when introducing fluorine into the PDMS coating. Bacterial adhesion to surfaces has been attributed to many factors, including surface chemical composition [42,43], surface hydrophilicity [44], surface roughness [45], and surface mechanical properties [46]. As no significant differences in surface roughness were detected between untreated and plasma treated samples (Figure 6), the differences observed in bacteria attachment cannot be attributed to differences in surface morphology.…”
Section: Marine Bacteria: Attachment and Adhesion Strengthmentioning
confidence: 99%
“…18 Bacterial adhesion can also be affected by properties such as roughness, stiffness, and topography. 20,21 Reducing bacterial adhesion on the inner lumen of the ETT could reduce biofilm formation and perhaps prevent further colonization of the tube itself.…”
Section: Introductionmentioning
confidence: 99%
“…The type, concentration, conformation, and bioactivity of proteins adsorbed onto a material depend on its topographical (roughness), chemical, physical (charge and hydrophilicity), and mechanical (stiffness) properties, all of which can be easily influenced by nanotechnology (2). Surface properties, including topography, also effect bacterial adhesion and may play an important role in the initial stages of biofilm formation (3,4).…”
mentioning
confidence: 99%